The applied SQL data analytics workshop : develop your practical skills and prepare to become a professional data analyst /: develop your practical skills and prepare to become a professional data analyst. ([2020]) - Goldwasser, Matt; Malik, Upom; (Computer scientist), Johnston, Benjamin
No abstract available